Molecular characterization of extended‐spectrum β‐lactamase, plasmid‐mediated AmpC cephalosporinase and carbapenemase genes amongEnterobacteriaceaeisolates in five medical centres of East and West Azerbaijan, Iran. Issue 11 (16th November 2016) - Sadeghi, Mohammad Reza; Ghotaslou, Reza; Akhi, Mohammad Taghi; Asgharzadeh, Mohammad; Hasani, Alka
Abstract : N/A: Very little is known about the occurrence and various types of extended‐spectrum β‐lactamase (ESBL), AmpC and carbapenemase in Iran. The aims of this study were to determine the prevalence of ESBLs, AmpCs and carbapenemase genes among Enterobacteriaceae in Azerbaijan and to characterize the genetic composition of the detected genes. A total of 307 Enterobacteriaceae isolates, recovered from five medical centres, were screened for ESBL, AmpC and carbapenemase activities by the disc diffusion method and phenotypic confirmatory tests. The 162 selected strains (third‐generation cephalosporins, cefoxitin‐ or carbapenem‐resistant strains with positive or negative phenotypic confirmatory tests) were selected for multiplex PCR screening for β‐lactamase genes, and detected genes were confirmed by sequencing. Of 162 isolates, 156 harboured 1 to 6 β‐lactamase genes of 41 types. The most prevalent genes were bla TEM‐1 (29.9 %), followed by bla CTX‐M‐15 (25.7 %). Plasmid‐mediated AmpC was detected in 66 strains (21.5 %) alone or in combination with other genes. Carbapenemase‐encoding genes were detected in 18 strains (5.8 %) of 27 carbapenem‐non‐susceptible isolates including 11, 7, 3 and 1 cases of bla OXA‐48, bla NDM‐1, bla KPC‐2 and bla KPC‐3 genes, respectively. Interestingly, 148 (94.8 %) of 156 strains with any β‐lactamase gene were found to have a multidrug‐resistant pattern. The rate of resistance to β‐lactams and multidrug‐resistant Enterobacteriaceae is high in Azerbaijan. All positive strains for carbapenemase genes were resistant to all β‐lactams. The present study reveals the high occurrence of CTX‐M‐type ESBLs followed by TEM and SHV variants among Enterobacteriaceae isolates. East Azerbaijan seems to be an alarming focus for OXA‐48, NDM‐1 and KPC dissemination.